THE INFLUENCE OF WORK COMPENSATION AND MOTIVATION TOWARD EMPLOYEE PERFORMANCE IN KRAKATAU MEDIKA HOSPITAL IN CILEGON CITY - Adissya Maya Andara (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2022)
This study aims to determine the effect of compensation on employee performance, to determine the effect of work motivation on employee performance and to determine the effect of compensation and work motivation together on employee performance in the Inpatient Division at Krakatau Medika Hospital in Cilegon City. This study uses quantitative research methods, quantitative research methods can be interpreted as research methods based on the philosophy of positivism, used to examine populations or specific samples, sampling techniques are generally carried out randomly, data collection using research instruments, quantitative data analysis / statistics in order to test the hypothesis set. As for the population in this study were employees in the Inpatient Division at Krakatau Medika Hospital in Cilegon City as many as 47 employees while the sample used a saturated sample that took all of the total population of 47 employees in the Inpatient Division at Krakatau Medika Hospital in Cilegon City. Based on the results obtained in hypothesis one, there is a significant effect of compensation on employee performance in the Inpatient Division at Krakatau Medika Hospital in Cilegon, the result of tcount> ttable (3,557> 2,014) with a significance level of 0.00 (0.00 <0 , 05) with a correlation value of 0.473 with a positive direction this means that if compensation increases it will improve employee performance, hypothesis two there is a significant influence of work motivation on employee performance in the Inpatient Division at Krakatau Medika Hospital in Cilegon, the result of tcount> ttable (5.148> 2.014) with a significance level of 0.00 (0.00 <0.05) with a correlation value of 0.613 with a positive direction this means that if work motivation increases it will improve employee performance and hypothesis 3 there is a significant influence between compensation and work motivation together on employee performance in the Raw Division at Hospitalization at Krakatau Medika Hospital in Cilegon, the result of Fcount> Ftable (21,278> 2.761) with a significance level of 0.00 (0.00 <0.05) while the coefficient of determination of 0.527 means that the compensation and work motivation variables affect 52.7% of employee performance while the remaining 47.3% is influenced by other factors not examined in this study.